What's new

Formula for CCX-Basis Spread

rishivala

New Member
Hi,

I would appreciate some assistance with disentangling the formula for basis spread from the reading - Covered Interest Rate Parity Lost: Understanding Cross-Currency Basis.

EQN 1: F/S = (1 + r + b) / (1 + r*) --> This is CIP with the inclusion of the basis spread (b)

The reading shows that when r* approx 0 then:
EQN 2: b = (F - S)/S - (r - r*)

How did the writer go from EQN 1 to 2? From my own algebra I get:
F/S * (1 + r*) = 1 + r + b --> [ (1 + r*) = 1 because r* = 0]
F/S - 1 - r = b
(F-S)/S - r = b
 
Top